The burden of disease in seronegative myasthenia gravis: a patient-centered perspective - Lehnerer, Sophie; Stegherr, Regina; Grittner, Ulrike; Stein, Maike; Gerischer, Lea; Stascheit, Frauke; Herdick, Meret; Doksani, Paolo; Meisel, Andreas; Hoffmann, Sarah (Frontiers in Immunology, 2025)
ObjectiveMyasthenia gravis (MG) is an autoimmune disorder primarily caused by autoantibodies against the acetylcholine receptor (AChR). Approximately 15% of MG patients, categorized as seronegative (snMG), lack detectable antibodies. Due to the snMG status, there may be a diagnostic delay. Moreover, there are limited data on treatment response in comparison to AChR-Ab+ patients. This study examines the burden of disease, treatment response, and quality of life of snMG patients in comparison to AChR-ab+ MG patients and healthy controls.MethodsA questionnaire-based survey was conducted collecting sociodemographic and clinical data including antibody status, therapy, treatment response, and self-rated disease severity along with standardized assessments such as MG-ADL (activities of daily living) and the Short Form Health (SF-36, generic Health-Related Quality of Life, HRQoL). HRQoL was evaluated through matched-pairs analyses. Participants from a general health survey served as the control group. Negative binomial regression was applied to evaluate the impact of antibody status on MG-ADL.ResultsCompared to AChR-ab+ patients, snMG patients (n = 237) were younger at symptom onset [median age 42 (IQR 30.5/53) vs. 51 (31/64) years, p < 0.001] and had longer diagnostic delays. Complete stable remission was less frequent in snMG patients (15.9% vs. 27.8%, p < 0.001), and they reported higher disease severity (52.8% medium, 9.5% severe vs. 41.9% medium, 8.5% severe, p = 0.005). snMG patients had higher MG-ADL scores [median 5 (IQR 2/9) vs. 3 (1/6), p < 0.001] and more employment restrictions (64.4% vs. 49.3%, p < 0.001). Furthermore, compared to healthy controls, snMG patients showed worse outcomes in all domains of the SF-36.ConclusionThe burden of disease in snMG patients is higher compared to AChR-ab+ MG due to delay in diagnosis, worse treatment response, and sociodemographic factors. These findings highlight the challenges patients and treating physicians face in snMG. There is a high need for earlier diagnosis, improved diagnostic tools, and inclusion of snMG patients in clinical trials to address their unique therapeutic challenges.Clinical Trial Registrationclinicaltrials.gov, identifier NCT03979521. Registered 7 June 2019 (retrospectively registered).